The translation of English tourism news text into Indonesian - Ni Nyoman Deni Ariyaningsih; I Dewa Ayu Devi Maharani Santika (English, 2018)
Translating a text could be done by those who have knowledge about the source language and the target language of a text. The fourth-semester students of STIBA Saraswati Denpasar can be also said to able to do a translation. For this research, the text about tourism is given, since they have already taken the English for tourism subject, and it is hoped that they will understand the special terms of tourism well. This research applied descriptive qualitative, using the data source from the translations of tourism text entitled “Strolling Relaxingly on the Shore of Kuta Beach, President Jokowi Assured that Bali is Safe to Visit” into Indonesian. The research focuses on finding the translation procedure conducted by the students in translating the text and analyzes the reason for applying those procedures by using the theory of translation procedures from Newmark (1988). The result of this research shows that there are three procedures applied mostly by the students in translating the text. First is naturalization because many words in the text were translated into the same terms in the source language, but they have changes in morphology form in the target language. Second is through translation because the students were likely to translate the text literarily following the structure of the sentences in the source text. Meanwhile, the other procedures applied were cultural equivalent, shift/transposition, and transference.